Patterned surface charges coupled with thermal gradients may create giant augmentations of solute dispersion in electro-osmosis of viscoelastic fluids. (31st January 2019) - Mukherjee, Siddhartha; Dhar, Jayabrata; DasGupta, Sunando; Chakraborty, Suman
Abstract : Augmenting the dispersion of a solute species and fluidic mixing remains a challenging proposition in electrically actuated microfluidic devices, primarily due to an inherent plug-like nature of the velocity profile under uniform surface charge conditions. While a judicious patterning of surface charges may obviate some of the concerning challenges, the consequent improvement in solute dispersion may turn out to be marginal. Here, we show that by exploiting a unique coupling of patterned surface charges with intrinsically induced thermal gradients, it may be possible to realize giant augmentations in solute dispersion in electro-osmotic flows. This is effectively mediated by the phenomena of Joule heating and surface heat dissipation, so as to induce local variations in electrical properties. Combined with the rheological premises of a viscoelastic fluid that are typically reminiscent of common biofluids handled in lab-on-a-chip-based micro-devices, our results demonstrate that the consequent electro-hydrodynamic forcing may open up favourable windows for augmented hydrodynamic dispersion, which has not yet been unveiled.